An econometric model of the Japanese balance of payments and its policy implications - Amano, Akihiro (Tokyo: Japan Economic Research Center, 1973)
The book was a study to explore the determinants and the characteristics of adjustment process of the Japanese balance of payments by estimating and working a quarterly econometric model.
Includes bibliographic footnotes.
usc 20/07/18
Loans
Keywords: Balance of payments; Balance of payments--Econometric models; Economic history; Japan